The impact of the use of technical devices in the development of some variables and starting to learn the long jump with middle school students - Mohammed , Abdul Salam (Journal of Physical Education, 2012)
The effectiveness of the long jump in particular can be used by the media multiple technology in order to create an opportunity to develop the performance of the learner through the preparation of a learning environment can interact with the learner in the educational program includes technical information on performance and mechanical advancement and the requirements of the conditions of a private body is moving in the application technical performance and the achievement of achievement with the help of computer-mail that gives the learner the right to control information that appears on the screen and the time of its appearance and the freedom of roaming in the tutorial. Therefore, the importance of research comes from the multi-link multimedia educational audio and video in an educational program using a computer in accordance with the special education environment. This trend in the educational process is believed to be not dealt with earlier, and on the other could answer several questions, including the reduction of the time when the educational use of this environment. Mamdy degree and master the technical and mechanical performance.Economy as well as effort. Preparation of a learning environment through the collection and media education integrated with each other through the computer to make education more effective in the long jump skills. So research aimed at identifying the impact of these media in the development of performance art and mechanical skill to improve the long jump for the students.Kzl and identify the differences in the level of performance before and after application of the learning environment. And the imposition of the researcher in that there are significant differences in test results before and after the performance level of the long jump after using the learning environment proposed, as well as no significant differences in test results before and after the angles of departure and the situation and the direction of the takeoff after the use of the learning environment proposed. And applied research on a sample of middle school students to raise Karkh / 1 hit (20) Tabaka divided into two groups. And held a researcher tests the performance and technical analysis video for the angles of departure and the situation and the direction and applied exercises educational computer-assisted and photographs for the period from 5/10 until 27/11/2011, and left a number of conclusions including that feedback using technical devices have helped to master the stages of technical and achievement Balothb long sample Search .